1515. Patient-Based Stratification of Weighted-Incidence Syndromic Antibiogram (WISCA) for Empiric Antibiotic Prescribing. (26th November 2018) - Hebert, Courtney; Hade, Erinn; Rahman, Protiva; Lustberg, Mark; Dewart, Courtney; Pancholi, Preeti; Stevenson, Kurt
Abstract: Background: Antibiograms are often stratified by location (e.g., ICU) to better assess resistance risk of patients in those locations (1). A weighted-incidence syndromic antibiogram (WISCA) may be more useful for empiric prescribing in that it stratifies on syndrome (e.g., urinary tract infection (UTI)) and calculates coverage over all organisms (i.e., weighted incidence). Here we explore the impact of stratification by admission location and patient-specific factors. We suggest that with the availability of patient data from EHRs historic microbiology data can be stratified by syndrome and patient-level factors, making them available for empiric decision support. Methods: The cohort included patients admitted from November 1, 2011 to July 1, 2016, with a positive urine culture in the first 48 hours and a diagnosis of UTI. Data on admission from a nursing facility (SNF), intensive care unit (ICU) stay in the first 24 hours of admission and antibiotic use in the last 30 days were extracted from the local data warehouse. Expert consensus enriched the susceptibility information that was not reported for organism-antibiotic pairs. The most recent admission for each patient was included. Antibiotic coverage was compared between strata by a chi-square test. Results: Of the 6, 366 patients with UTI, 13% were admitted to an ICU; 8% were admitted from an SNF and 44% had exposure to antibiotics in the last 30 days. Antibiotic coverage did not significantly differ between ICU and non-ICU patient admissions. However, those admitted from an SNF and those admitted with antibiotic exposure in the past 30 days had lower levels of coverage to all antibiotics under study. Conclusion: Our findings suggest that stratifying by patient factors, easily obtainable from the EHR, may provide more useful empiric prescribing information than stratifying by ICU location. Research reported in this publication was supported by the National Institute of Allergy and Infectious Diseases of the NIH under Award Number R01AI116975. Reference 1. Clinical Infectious Diseases 2007; 44:867–73 Disclosures: All authors: No reported disclosures.